Acute hepatitis E in French patients and neurological manifestations. Issue 3 (September 2018) - Abravanel, Florence; Pique, Julie; Couturier, Elisabeth; Nicot, Florence; Dimeglio, Chloé; Lhomme, Sébastien; Chiabrando, Julie; Saune, Karine; Péron, Jean-Marie; Kamar, Nassim; Evrard, Solène; de Valk, Henriette; et al.
Highlights: A case-control study identified the risk factors involved in French HEV infection. HEV infection was associated with contact with farm animals, eating pork liver sausage and eating unpeeled fruit. Neurological manifestations were more frequent in immunocompetent patients. Neuropathic pain suggesting small fiber neuropathy was frequently reported. Summary: Objectives: Hepatitis E virus (HEV) is a major cause of acute hepatitis worldwide. However, our understanding of the source of contamination is incomplete and the frequency of neurological manifestations in still unknown. Methods: 200 eligible cases reported to the French National Reference Center from January 2015 to December 2015 were prospectively included in this case-control study (1 case: 1 control, matched for sex, age and area of living) to investigate the risk of infection. We documented the factors associated with their HEV infection and clinical manifestations. Results: The 200 HEV-infected patients included 137 who were immunocompetent and 63 immunocompromised. The factors associated with an HEV infection were contact with farm animals, eating pork liver sausage and eating unpeeled fruit. The 33 patients (16.5%) who reported neurological symptoms included 14 with neuropathic pain suggesting small fiber neuropathy, 9 with painless sensory disorders, 6 with Parsonage–Turner syndrome, one Guillain–Barre syndrome, one meningitis, one encephalitis and one diplopia. Neurological manifestations were more frequent in immunocompetent patients (22.6% vs 3.2%, p < 0.001). Conclusions: This study highlights the risk of HEV transmission by the environment in industrialized countries. The higher frequency of neurological disorders in immunocompetent patients suggests pathophysiological mechanisms involving the immune system.